Desain Sistem Informasi Rekam Medis Digital untuk Optimalisasi Pelaporan Imunisasi Bayi Baru Lahir di Puskesmas Gunung Sembung - Chicy Indah Sari; Yuyun Yunengsih; Falaah Abdussalaam (Indonesian Journal of Computer Science and Engineering, 2025)
This study aims to develop a medical record information system that supports faster and more accurate reporting of newborn immunization data at Gunung Sembung Public Health Center (Puskesmas). The identified issue involves the mixing of newborn vaccination data with that of older children, alongside a manual reporting process that hampers timely submissions to the Health Office. A descriptive qualitative approach was employed, with data collected through observation, interviews, and literature review. The system development followed the V-Model methodology within the Software Development Life Cycle (SDLC) framework. The results show that the developed system improves efficiency and accuracy in newborn immunization reporting. It is recommended that the system be implemented sustainably and further enhanced to support broader health data integration.